AMAP Progress Report. 30 April 2010 – 1 October 2010. Senior Arctic Officials Meeting. Tórshavn, Faroe Islands, 19 – 20 October 2010. - Arctic Monitoring and Assessment Programme (AMAP) (Arctic Monitoring and Assessment Programme (AMAP), 2010)
Arctic Council working group Arctic Monitoring and Assessment Programme (AMAP)s progress report, delivered to Arctic Council's Senior Arctic Officials meeting in Tórshavn, Faroe Islands, October 19-20 2010.